Cancer incidence in northern Thailand: Results from six population‐based cancer registries 1993–2012. Issue 9 (28th December 2017) - Pongnikorn, Donsuk; Daoprasert, Karnchana; Waisri, Narate; Laversanne, Mathieu; Bray, Freddie
Abstract : Rapid changes in social and economic development have led to cancer becoming a major cause of national morbidity and mortality in Thailand. Cancer registries have been critical in documenting subnational cancer patterns and transitions in the country; with the establishment of six registries in northern Thailand, a comprehensive assessment of the scale and profile of cancer is now possible in the region. Cancers of the liver, lung, colorectum, breast and cervix were the major cancers 2008–2012, although variations in the profiles of cancer were observed, with a very high incidence of liver cancer seen among males in Phrae, corresponding to one in 11 men developing the disease in a lifetime. Based on data from Lampang and Chiang Mai 1993–2012, rates of lung and cervical cancer incidence have declined, while liver, colorectal and breast cancer incidence have been increasing up to 2012. A more detailed investigation of the incidence trends for specific cancer sites and subtypes at the local level are crucial to the monitoring and evaluation of the cancer control interventions implemented within the Thai national cancer control programme (NCCP). Priority should be given to extend the capacity of the new registries in northern Thailand, ensuring improvement in quality and utilization of the data to drive epidemiologic research and cancer control. Abstract : What's new? Population‐based cancer registries (PCBRs) and a national cancer control program have been instrumental in facilitating the collection of cancer data in Thailand. Growth in cancer surveillance has been especially significant in northern Thailand, which house six PCBRs, several established only within the last 15 years. In our study, cancer trends and burden in northern Thailand were assessed from PCBR data for the period 1993–2012. The data show that overall while lung and cervical cancer incidence rates declined, colorectal and breast cancer incidence increased. From 2008 to 2012, liver, lung, colorectal, breast and cervical cancers were the major cancers in the region.